Land resources management and soil degradation factors in the Republic of Moldova - Tamara Leah (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Land resource management includes three interrelated levels: national, district and commune. The purpose and basic objectives are: state land policy implementation, legislation and regulations in force, effective implementation of measures to protect soil cover, to maintain ecological balance and biological diversity in ecosystems of the Republic of Moldova. The soil cover quality on the most agricultural land is unfavorable, and on some land - critical. Continue to expand the area affected by erosion and landslides, dehumification processes, damage of structure and compaction, sodium enrichment, salinization and soil swampy, drought intensified. Land management in the Republic of Moldova should be a process of development and implementation system of organizational, economic and administrative levers. They would allow regulation and development the forecast of quality land status; develop recommendations on the rational use of land, combating soil degradation processes and long-term preservation of agricultural production capacity. Basic information for proper management of land resources must become computerized information system of the state of soil quality.
Keywords: 330; agriculture; land recourses; soil cover; soil degradation; soil evaluation